Me and My House : James Baldwin's Last Decade in France - Zaborowska, Magdalena J. (Book collections on Project MUSE., 2018)
The last sixteen years of James Baldwin's life (1971-87) unfolded in a village in the South of France, in a sprawling house nicknamed "Chez Baldwin." In this volume, the author employs Baldwin's home space as a lens through which to expand his biography and explore the politics and poetics of blackness, queerness, and domesticity in his complex and underappreciated later works. The author shows how the themes of dwelling and black queer male sexuality in "The Welcome Table," "Just above My Head," and "If Beale Street Could Talk" directly stem from Chez Baldwin's influence on the writer. The house was partially torn down in 2014. Accessible, heavily illustrated, and drawing on interviews with Baldwin's friends and lovers, unpublished letters, and manuscripts, this volume offers new insights into Baldwin's life, writing, and relationships, making it essential reading for all students, scholars, and fans of Baldwin.